Relationship between pelvic tilt and landing mechanics in division I male and female student athletes - Calovini, A.; Wang, D.; Sell, K.; Karas, L.; Leek, C.; Shaver, K.; Gonzalez, A.; Ghigiarelli, J.; Pottorf, O. (International Journal of Exercise Science Conference Proceedings, 2025)
The pelvic-hip complex serves as a central component in the kinetic chain, facilitating load distribution and linking the upper and lower body. Prior research has indicated that atypical pelvic tilt (PT) is associated with compensatory activation in surrounding musculature, however the relationship between PT and landing mechanics is sparse.